Perspectives for European Democracy After the Lisbon Treaty – Pan-European Instruments of Deliberative and Participatory Democracy in the EU - Panayotova, Monika (Research Papers, 2022)
The paper focuses on the unique nature of the EU as “sui generis” organization and the world's first transnational democracy. It analyses the emergence of Pan-European instruments of deliberative and participatory democracy, namely the Conference on the Future of Europe and the European Citizens' Initiative, as well as the ideas of transnational lists and Spitzenkandidaten process. Thus, it demonstrates the evolution of the EU democracy since the Lisbon Treaty and the potential for its modernisation within the Treaties. Considering the forthcoming European elections2024, it is recalled that democracy {~~relays~>relies~~} on citizens’ empathy and the ability of politicians to listen to “the vox populi”, showing them that their opinion matters.
Keywords: European democracy; Conference on the future of europe; European citizens’ initiative; Transnational lists; Spitzenkandidaten; Lisbon treaty; European elections; EU institutions; Future of Europe